Macroscale abundance patterns of hydromedusae in the temperate Southwestern Atlantic (27º-56º S) - Dutto, María Sofía (2019)
Gelatinous organisms are crucial components of marine ecosystems and some species imply social and economic consequences. However, certain geographic areas, such as the temperate Southwestern Atlantic (SWA, 27 - 56 S), remain understudied in terms of jellyfish ecological data. We analyzed 3,727 plankton samples collected along ~6.7 million km2 over a 31-year period (1983–2014) to determine the occurrence, abundance, and diversity patterns of hydromedusae in the SWA. Analyses were made at both community and species levels. Two abundance hot spots of hydromedusae were identified, where values up to 2,480 ind. m-3 were recorded between 2003 and 2014. Liriope tetraphylla and Obelia spp. were the main responsible for recurrent peaks. Diversity indexes were in the range of those published for temperate areas worldwide, and some coastal zones showed values that can be considered moderate to high for a temperate neritic region. The community analysis yielded 10 groups following previously determined biogeographic schemes throughout the study area. This work enhances the knowledge of hydromedusae in the SWA and provides essential information about the current global warming context and the gelatinous zooplankton data necessity.